Nora's ark - Spinelli, Eileen; Hilb, Nora (Grand Rapids, Mich. : Zonderkidz, 2012)
When the weatherman predicts rain, young Nora builds an ark just like Noah's--almost.
Ages 4-7.
Keywords: Noah's ark -- Fiction; Play -- Fiction; Imagination -- Fiction; Noah's ark -- Juvenile fiction; Play -- Juvenile fiction; Imagination -- Juvenile fiction; Imagination; Noah's ark; Play; Fiction; Juvenile works